Trans-Oral Robotic Surgery in the Management of a Supraglottic Solitary Fibrous Tumor. Issue 5 (July 2020) - De Virgilio, Armando; Mercante, Giuseppe; Costantino, Andrea; Pellini, Raul; Petruzzi, Gerardo; Yiu, Philip; Gaino, Francesca; Spriano, Giuseppe
Abstract : Abstract: Trans-oral robotic surgery (TORS) has become increasingly widespread for the head and neck surgery procedures. In this paper, the authors describe the first reported TORS in the management of a laryngeal solitary fibrous tumor (SFT). A 77-year-old woman suffered from progressive dysphonia lasting 2 years and occasional dyspnea. A submucosal mass of about 4 cm in diameter involving the left supraglottis and left aryepiglottic fold was detected during the flexible fibre-optic laryngeal examination. Magnetic resonance imaging revealed a solid, well-demarcated mass (36 × 25 mm), hyperintense with nonhomogeneous contrast enhancement in T2-weighted sequences. The lesion was successfully removed en bloc using the daVinci Xi system (Intuitive Surgical, Sunnyvale, CA) equipped with 3 robotic arms (1 3-dimensional endoscopic arm, 1 monopolar cautery, 1 bipolar Maryland forceps). The postoperative course was regular, and the endoscopic examination at 1 month showed normal laryngeal morphology and function. Trans-oral robotic surgery has proved to be a good alternative to conventional trans-oral approaches in the treatment of laryngeal SFT. The lesion was completely removed without intraoperative complications, and postoperative morbidity was minimized. Further comparative studies are recommended to define if TORS could become the gold standard for the surgical treatment of laryngeal SFTs. Abstract : Supplemental Digital Content is available in the text